1986
DOI: 10.3354/meps032035
|View full text |Cite
|
Sign up to set email alerts
|

Importance of predatory infauna in marine soft-sediment communities

Abstract: Ambrose (1984a) suggested that a 3-way interactive model should be applied to marine infaunal communities having the levels of epibenttuc predators, predatory infauna and nonpredatory infauna. It is shown that the 3-level interactive model incorporates the implicit, unstated assumption that epibenthlc predators preferentially prey on predatory infauna. A review of the literature reveals that this assumption is not true. The assumption of predatory infauna being more susceptible to epibenthic predation is chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Third, as consumers of infaunal predatory worms, variation in the abundance of fish in the guild alters the ratio of infaunal predators to infaunal prey. Although the validity of these altered ratios is open to question (see Ambrose 1984, Wilson 1986), the shifts in ratios that we observed in the predator exclusion experiment indicate that nonlinear effects on community structure occur with variation in fish predation intensity. In areas of inherently low diversity like the upper reaches of estuaries, these shifts in species composition may be of considerable consequence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, as consumers of infaunal predatory worms, variation in the abundance of fish in the guild alters the ratio of infaunal predators to infaunal prey. Although the validity of these altered ratios is open to question (see Ambrose 1984, Wilson 1986), the shifts in ratios that we observed in the predator exclusion experiment indicate that nonlinear effects on community structure occur with variation in fish predation intensity. In areas of inherently low diversity like the upper reaches of estuaries, these shifts in species composition may be of considerable consequence.…”
Section: Discussionmentioning
confidence: 97%
“…mean abundances of each dependent variable (log abundance of each infaunal species) were tested for differences among cage treatments at each of the 5 stations using Tukey's simultaneous test for unplanned multiple comparison of means with unequal sample sizes (see Day & Quinn 1989) as modified by Cicchetti (1972) to avoid confounde d comparisons. To test whether re duction in predation pressure by epibenthic fish and crabs enhanced infaunal predatory versus non-predatory species (see Ambrose 1984, Wilson 1986). differences in the ratio of infaunal predators (Nereis succinea + Eteone h eteropoda x Carinoma tremaphorus) to infaunal prey (sum of other species) among treatments, stations, and their interaction were tested by ANOV A after Fmax tests of arcsine-squareroot transformed data indicated homogeneity of data.…”
Section: Methodsmentioning
confidence: 99%
“…I initially tested this model by comparing the ratio of the abundance of predatory infauna to nonpredatory infauna in the presence and absence of epibenthic predators and found that the ratio Increased as predicted following the removal of epibenthic predators. Wilson (1986) demonstrates that preferential predation on predatory infauna by epibenthic predators is a requirement of the 3-level model, but finds no support for such predation in the literature. Wilson also reanalyzes the data set I used to test my model using a different definition of predatory infauna and finds no significant difference in the ratio of predatory infauna to non-predatory infauna between caged and uncaged areas.…”
Section: Introductionmentioning
confidence: 88%
“…By modeling the effects of preferential and nonpreferential predation on the ratio of predatory infauna to non-predatory infauna, Wilson (1986) shows that the 3-level model depends on preferential predation. Wilson's model, however, is inexact because it does not use a continuous function to analyze changes in the ratio of predatory to non-predatory infauna.…”
Section: Mechanism Of Proposed Interactionsmentioning
confidence: 99%
“…crabs, shrimps, fishes) and infaunal prey, and instead proposed an additional 'predatory infauna' level that mediates the interactions between top epibenthic and non-predatory infauna. Wilson (1986) questioned this view, arguing that in order to verify the existence of such trophic complexity in soft sediments, top (epibenthic) predators should display strong preference for predatory infaunal species. Our design was not intended to resolve this debate, but using Wilson's arguments, our results clearly support the view of Ambrose (1984): P. tecta was several times more abundant in exclusion than in predator treatments, both in field and in laboratory experiments.…”
Section: Influence On Species Compositionmentioning
confidence: 99%